Mehr Plan- als Marktwirtschaft in der energiepolitischen Strategie 2020 der Europäischen Kommission - Justus Haucap; Michael Coenen (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2011)
The Europeanization of energy policies is desirable because the three main objectives of energy policy (climate protection, security of supply and competitiveness) have cross-border impacts. Hence, it is good that the European Union has been granted a competence for energy policy in the article 194 of the Lisbon treaty. In addition, it is good that the European Commission has published its long-term strategy to stabilize expectations which is important for infrastructure investment. It is regrettable though that price signals, competition and market principles only play a minor role for the Commission while rather doubtful objectives such as fostering energy efficiency and promoting renewable dominate the agenda. The Commission's strategy is mainly characterized by bureaucratic dirigisme, intense regulation, state planning and public subsidies. The road to a centrally planned energy industry is being walked down fast.
Keywords: L94; Q48; Q58; 330